2014
DOI: 10.1016/j.bios.2013.08.048
|View full text |Cite
|
Sign up to set email alerts
|

Conductance based sensing and analysis of soluble phosphates in wastewater

Abstract: The current standard method used for measuring soluble phosphate in environmental water samples is based on a colourimetric approach, developed in the early 1960s. In order to provide an alternative, label free sensing solution, a molecularly imprinted polymer (MIP) was designed to function as a phosphate receptor. A combination of functional monomer (N-allylthiourea), cross-linker and monomer/template ratios were optimised in order to maximise the binding capacity for phosphate. When produced in membrane form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 33 publications
0
12
1
Order By: Relevance
“…Any removal of phosphate found was typically associated with standard error. The results from this study corresponds those reported byWarwick et al (2014a) who indicated that TU NIP was able to remove only 1% phosphate at C0 = 0.78 mg PO4 3-/L. However, this contradicts the same work done byWarwick et al (2014a) who reported the TU MIP removing 22% phosphate at C0 = 0.78 mg PO4 3entirely surprising asWarwick et al (2014a) also reported large error associated with phosphate removal by TU MIP.…”
contrasting
confidence: 54%
See 1 more Smart Citation
“…Any removal of phosphate found was typically associated with standard error. The results from this study corresponds those reported byWarwick et al (2014a) who indicated that TU NIP was able to remove only 1% phosphate at C0 = 0.78 mg PO4 3-/L. However, this contradicts the same work done byWarwick et al (2014a) who reported the TU MIP removing 22% phosphate at C0 = 0.78 mg PO4 3entirely surprising asWarwick et al (2014a) also reported large error associated with phosphate removal by TU MIP.…”
contrasting
confidence: 54%
“…Lastly, the thiourea imprinted polymer showed to bind 22% of the phosphate, while the non-imprinted polymer (NIP) only bound 1%. This was, however, not entirely convincing of thiourea's ability to be effectively imprinted as the thiourea MIP deviated largely from the mean (Warwick et al, 2014a). trimethylolpropane trimethacrylate (TRIM) were compared.…”
Section: Phosphate Imprintingmentioning
confidence: 99%
“…Experiments using various phosphate concentrations in deionised water (0.03 to 31 mg P L -1 ) were completed to assess the relationship between the change in conductance produced with concentration and a correlation (r 2 ) of 0.97 was established. Furthermore the MIP sensor selectively detected the presence of phosphate compared to sulphate, nitrate and chloride and the binding was found to be reversible, enabling the re-use of the membrane for multiple measurements (Warwick et al, 2013b).…”
Section: Optimisation Of the Thiourea Based Mip And Integration Into mentioning
confidence: 99%
“…The functionalizationof polymer surfaces with molecular recognition capability gained attention due to the potential usage of molecularly imprinted polymersfor analytical applications [28]. The surface grafting methodology increases the accessibility of the target moleculeto the binding sites when compared to bulk polymerization.…”
Section: Surface Imprinted Polymersmentioning
confidence: 99%